Analysis of Students’ Learning Style Preference Adaptation on Mathematics Learning during the Distance Learning Condition - Nugraha, Trisna; Prabawanto, Sufyani (Universitas Sebelas Maret, 2021)
Changes in the education system due to COVID-19 pandemic through distance learning (PJJ) have made it difficult to accommodate students’ needs in achieving mathematical proficiency. The needs of these students are based on students learning style preference (KGB), how students obtain information, as one of the determinants of success in learning mathematics. This study aims to investigate the extent to which each student’s KGB can adapt to the PJJ designed through RADEC (Read-Answer-Discuss-Explain-Create) and direct learning. A quasi-experimental study with 2 x 3 factorial designed was conducted involving 56 4th graders from a private elementary school in Bandung. The research instrument used was the KGB scale and mathematical conceptual understanding (MCU) test. The result of this study showed that there were differences in students’ MCU viewed by KGB during PJJ which was more accommodating to visual students. It is necessary to improve the PJJ design that accommodate each KGB.